Peperomia (Piperaceae) novelties from Veracruz State, Mexico - Mathieu, Guido; Vergara-Rodriguez, Daniela; Krömer, Thorsten; Karger, Dirk Nikolaus (Phytotaxa, 2015)
The preparation of a taxonomic treatment of the genus Peperomia (Piperaceae) for the ‘Flora of Veracruz’, revealed that three species remained without being described. This finding is a result of the review and study of botanical collections in several Mexican and foreign herbaria, as well as of field work in order to collect living and fertile material, which allowed us to describe and illustrate the species as new to science. Two of these, P. chazaroi and P. vazquezii, appear to be endemic to Veracruz, whereas P. parastriata was also found in the neighboring states Chiapas and Oaxaca. The treatment includes assessments of conservation status considering IUCN Red List criteria.